Muscle histochemistry in chronic alcoholism - M. L. Ferraz; A. A. Gabbai; A. S. B. Oliveira; A. P. J. Ferrari; S. J. Miszputen; A. Ferreira Neto; A. Castelo Filho; B. Schmidt (Arquivos de Neuro-Psiquiatria)
Twenty-two chronic acoholic patients were assessed by neurologic examination and muscle biopsy. The patients manifested proximal muscular weakness to a variable extent. One case presented as an acute bout of myopathy, according to the Manual Muscle Test, MMT. The most prominent histologic feature observed was muscle atrophy (95.3%) better evidenced through the ATPase stain with the predominance of type II A fibers (71.4%). Lack of the mosaic pattern (type grouping) seen in 76% of the cases and an important mitochondrial proliferation with intrasarcoplasmatic lipid accumulation in 63% of the patients. In case of acute presentation of muscle weakness the. pathological substrate is quite different, i.e. presence of myositis mainly interstitial characterized by lymphoplasmocytic infiltrate and several spots of necrosis like Zencker degeneration. Based on histologic criteria, our data suggest that: the main determinant of muscle weakness seen in chronic alcoholic patients is neurogenic in origin (alcoholic polineuropathy); the direct toxic action of ethanol under the skeletal muscle is closely related to the mitochondrial metabolism; the so-called acute alcoholic myopathy has probably viral etiology.